Peer-to-peer electricity trading: A systematic review on current developments and perspectives. (March 2023) - Bukar, Abba Lawan; Hamza, Mukhtar Fatihu; Ayub, Sara; Abobaker, Abobaker Kikki; Modu, Babangida; Mohseni, Soheil; Brent, Alan C.; Ogbonnaya, Chukwuma; Mustapha, Kunduli; Idakwo, Harrison Oyibo
Abstract: Peer-to-peer (P2P) electricity trading has become the next generation of energy management strategies that economically benefit prosumers by trading electricity as goods and services. The P2P electricity market is expected to support the grid to minimize reserve requirements, lower investment and operational costs, reduce peak demand, and improve reliability. Nonetheless, the deployment of P2P electricity trading in the electricity networks is challenging in terms of modelling the transactions in both the physical and virtual layers of the network. The physical layer is a physical network that enables the transfer of electricity from the sellers to the buyers once financial settlements between both parties are completed over the virtual layer platform. The virtual layer facilitates a secured connection for participants to decide on their electricity trading parameters. This paper systematically reviews the current developments in the P2P electricity trading literature. Importantly, the systematic literature review brings to light six essential components in P2P electricity trading processes, namely: P2P electricity trading platforms, P2P market schemes, P2P electricity trading market clearance algorithms, policy supporting P2P electricity trading, P2P electricity trading networks and P2P ICT infrastructure, which are discussed in detail in the paper. Accordingly, for each component, state-of-the-art technologies, notable findings, and best practice insights are comprehensively reviewed, based on which directions for future research are presented. The P2P electricity market is a rapidly emerging research domain with significant opportunities and prospects globally in the industry and academia.